Innovative approaches to soil health: evaluating pruning waste compost, inoculated compost, and mineral fertilizer in a controlled growth chamber for sustainable vineyard practices - Lucchetta, M.; Zuluaga, M. Y. A.; Monterisi, S.; Fattorini, R.; Gaiotti, F.; Cesco, S.; Pii, Y. (Frontiers in Sustainable Food Systems, 2025)
Healthy and fertile soils are the foundation of sustainable global agriculture, supporting both intensive and extensive crop cultivation, including orchards and vineyards across diverse agroecosystems. However, widespread use of synthetic fertilizers has degraded soil organic matter and overall quality, leading to significant environmental consequences and threats to ecosystem services. Challenges in accessing mineral fertilizers, along with growing concerns over environmental sustainability, have driven interest in alternative approaches such as compost, biofertilizers, biopesticides, and microbiome-based strategies to enhance soil fertility and reduce chemical inputs in agriculture. Compost derived from grapevine pruning waste shows promise in addressing agricultural challenges, but further research is needed to understand its effects on nutrient release dynamics and microbial activity. Inoculating compost with a fungal consortium presents an innovative strategy to enhance nutrient cycling and microbial interactions, addressing nutrient availability challenges. This study aimed to evaluate the impact of three fertilization methods on soil health: NPK (mineral fertilizer), PWC (pruning waste compost), and iPWC (pruning waste compost inoculated with fungal consortia). Conducted over 135 days in a controlled growth chamber, fifteen pots received equal macronutrient doses. Environmental parameters (humidity, temperature, light/dark cycles) were closely monitored. Throughout the experiment, release dynamics of key nutrients, soil enzyme activity, and microbial community responses were rigorously assessed. The results showed that compost inoculated with fungi significantly enhanced soil enzymes activities. Microbial community activity was higher in fungal and compost treatments, with greater functional diversity observed in the mineral fertilizer treatment. Compost released major minerals more slowly than chemical fertilizers, while enhancing the available fraction. These findings underscore compost’s potential, especially when supplemented with fungi, to improve soil health and promote sustainable agricultural practices and soil regeneration.